PP.40.04: WHITE COAT AND MASKED HYPERTENSION EFFECT IN TREATMENT RESISTANT HYPERTENSION. (June 2015) - Jumar, A.; Dechend, R.; Riemer, T.; Hagedorn, I.; Zeymer, U.; Schmieder, R.E.
Abstract : Objective: This analysis aimed to determine the prevalence of white coat and masked hypertension in patients with treatment resistant hypertension (TRH) in a real-life setting after treatment intensification on discretion of the treating physician. Design and method: In the 3A registry, a non-randomized, non-interventional registry, 899 physicians included 14.988 patients whose blood pressure (BP) was not controlled (> = 140/90 mmHg) and in whom the physician decided to initiate or escalate antihypertensive medication. Office BP and 24-hour ambulatory BP (ABP) were measured at baseline and at 1 year follow-up (FU) with validated devices. TRH was defined as uncontrolled BP at baseline despite treatment with at least 3 antihypertensive drugs. For this analysis TRH patients were classified by office BP (> = or < 140/90 mmHg) and 24-hour ABP (> = or < 130/80 mmHg) at 1 year FU. Results: After 1 year FU, i.e. after intensification of antihypertensive therapy, office and ABP was available in 1628 subjects. The cross-sectional analysis showed that nearly half of patients had controlled hypertension according to office BP. Masked (office BP < 140/90 mmHg and ABP > = 130/80 mmHg) and white coat hypertension (office BP > = 140/90 mmHg and ABP < 130/80 mmHg) effects at 1 year FU were the following: Figure. No caption available. Conclusions: After 1 year FU 2/3 of the apparently controlled hypertensives (office BP < 140 mmHg) had masked hypertension, and of the patients with apparent TRH (office BP >= 140/90 mmHg despite being on 3 drugs) 1/10 had white coat hypertension. Our data suggest the inclusion of 24-hour ABP for the treatment management.